DISSEMINATION OF COPYRIGHT LAW IN DIGITAL PRODUCTS IN SEMARANG CITY - Setiawan, Andry (Faculty of Law, Universitas Negeri Semarang, 2018)
A creative work created by its creator based on his sense and intention which is supported by his creativity will become an intellectual work with a high economic value. Such creators are like book and song writers who have an ability and idea to produce a work that can be enjoyed by everyone. Based on the principle of justice, it is understood that to produce such work is not an easy task because it requires sacrifice. Therefore, the creator is entitled to economic benefits for his work. An intellectual work having a very high economic value is supposed to get adequate legal protection supported by a sense of justice as the reward of the creator’s intellectual products. In addition to physical copyrighted work products, there are also digital products on which the creator owns a copyright. There are examples of digital products which follow the development of technology such as song files, e-books, software, etc. One of the problems that exists in the community is that the digital product becomes easier to be pirated or illegally downloaded through the internet. How is copyright protection in digital products as the embodiment of the creator's creative works. Copyright protection against creators and copyright holders pursuant to Act No. 28 of 2014 on Copyright. Article 1 number 1 and Article 24 paragraph (1) and (2). The creator or copyright holder has rights to be protected by the government, namely economic rights and moral rights. The existence of economic rights and moral rights is then someone's creative work will have its own values, so it is not easy to use his property for commercial purposes by the parties who are not responsible.